Electrically Conductive Hydrogel Nerve Guidance Conduits for Peripheral Nerve Regeneration. (12th August 2020) - Park, Junggeon; Jeon, Jin; Kim, Byongyeon; Lee, Min Suk; Park, Sihyeon; Lim, Juhan; Yi, Jongdarm; Lee, Hwangjae; Yang, Hee Seok; Lee, Jae Young
Abstract: Peripheral nerve injuries are serious conditions, and surgical treatment has critical limitations. Therefore, nerve guidance conduits (NGCs) are proposed as an alternative. In this study, multifunctional NGCs are fabricated for the regeneration of injured peripheral nerves. Graphene oxide (GO) and gelatin‐methacrylate (GelMA) are polymerized and chemically reduced to form reduced (GO/GelMA) (r(GO/GelMA)). The prepared materials present good electrical conductivity, flexibility, mechanical stability, and permeability, which are suitable for use as NGCs. In vitro studies show 2.1‐ and 1.4‐fold promotion of neuritogenesis of PC12 neuronal cells on r(GO/GelMA) compared to GelMA and unreduced GO/GelMA, respectively. Animal studies using a rat sciatic nerve injury model with a 10 mm gap between the proximal and distal regions of the defect reveal that r(GO/GelMA) NGCs significantly enhance peripheral nerve regeneration, indicated by improved muscle weight increase, electro‐conduction velocity, and sciatic nerve function index. Specifically, r(GO/GelMA) NGCs are utilized to potentiate regrowth with myelination in rat sciatic nerves followed by histological, immunohistological, and morphometrical analyses. This study successfully shows the feasibility of electrically conductive hydrogel NGCs as functional conduits for improved nerve regeneration in a preclinical study, where these NGCs can not only mimic nerve tissues but also strongly promote nerve regeneration. Abstract : Electrically conductive hydrogel‐based nerve guidance conduits are fabricated by polymerization of a graphene oxide (GO)‐incorporated gelatin‐methacrylate (GelMA) hydrogel, and subsequently chemically reduced. GelMA and reduced GO (rGO) show good tissue compatibility and can promote nerve regeneration. The r(GO/GelMA) conduit has the requirements of an ideal nerve guidance conduit with appropriate mechanical and electrical properties.